Predictive Modeling of TiN Coating Roughness - Mohamad Jaya, Abdul Syukor; Mohd Hashim, Siti Zaiton; Haron, Habibollah; Muhamad, Mohd Razali; Abd. Rahman, Md. Nizam; Hasan Basari, Abd Samad (Trans Tech Publication, Switzerland, 2013)
In this paper, an approach in modeling surface roughness of Titanium Nitrite (TiN) coating using Response Surface Method (RSM) is implemented. The TiN coatings were formed using Physical Vapor Deposition (PVD) sputtering process. N2 pressure, Argon pressure and turntable speed were selected as process variables. Coating surface roughness as an important coating characteristic was characterized using Atomic Force Microscopy (AFM) equipment. Analysis of variance (ANOVA) is used to determine the significant factors influencing resultant TiN coating roughness. Based on that, a quadratic polynomial model equation represented the process variables and coating roughness was developed. The result indicated that the actual coating roughness of validation runs data fell within the 90% prediction interval (PI) and the residual errors were very low. The findings from this study suggested that Argon pressure, quadratic term of N2 pressure, quadratic term of turntable speed, interaction between N2 pressure and turntable speed, and interaction between Argon pressure and turntable speed influenced the TiN coating surface roughness.